PREVALÊNCIA DE SINTOMAS SUGESTIVOS DE DEPRESSÃO EM IDOSOS QUE FREQUENTAM BAILES - Berlezi, Evelise M.; Stumm, Eniva M. F.; Battisti, Iara D. E.; Kirchner, Rosane M.; Hildebrandt, Leila M.; Leite, Marinês T. (Salão do Conhecimento, 2013)
Resumo